“Politieke erediens” as ruimte vir en kriterium van die lewe in evangeliese vryheid - Van der Merwe, IJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
“Political worship” as Space and Criterion for Life in the Freedom of the Gospel The church does not have a social ethic, she is a social ethic. The author argues that the church’s worship is of a political nature in the sense that it is the gathering of people with a dual citizenship. Connecting to, among others, the work of Wannenwetsch, it is shown that so-called “liturgical renewal” can actually obstruct the space in which renewal of the congregation is supposed to take place. It is further shown that worship can indeed be inauthentic if the political nature of worship is confused with the social involvement of the church in society.